(untitled) (Scientific journal of the Fergana State University, 2025)
The article examines the main strategies for integrating language learning and subject content within the CLIL (Content and Language Integrated Learning) methodology and their impact on the development of students’ professional communicative competence. Special attention is given to the use of visual effects and graphic organizers, project-based learning, and problem-solving approaches as effective tools for building both linguistic and subject competence. The analysis of practical case studies demonstrates that these strategies enhance students’ motivation, improve comprehension and retention of educational material, and foster critical thinking and language skills. The findings confirm the necessity of adapting approaches based on students’ language proficiency and the specific characteristics of the subjects being studied.